Analysis of Customer Satisfaction as a Determining Factor of Consumer Loyalty - Amelia Matondang (Patua : Journal of Business Administration and Management, 2025)
This study aims to analyze the role of Management Information Systems (MIS) in improving operational efficiency in the education sector. Along with the development of information technology, educational institutions are required to be able to manage data and operational processes effectively and efficiently. The research method used is a quantitative approach with a descriptive and explanatory design. Data were collected through the distribution of questionnaires to 80 respondents consisting of administrative and educational staff at educational institutions that have implemented MIS. Data analysis techniques include validity tests, reliability tests, descriptive analysis, and simple linear regression. The results of the study indicate that the Management Information System has a positive and significant effect on operational efficiency, with a regression coefficient value of 0.735 and a significance level of 0.000 (<0.05). The coefficient of determination value of 0.611 indicates that 61.1% of operational efficiency is influenced by the implementation of MIS, while the remainder is influenced by other factors outside the study. These findings indicate that the implementation of MIS can improve the speed of administrative processes, data accuracy, and the quality of decision-making in educational institutions. In conclusion, optimizing the use of Management Information Systems is a crucial factor in improving operational efficiency and the quality of educational services. Therefore, educational institutions are advised to continue developing and integrating information technology into their management processes to achieve more effective and sustainable performance.